Оценка состояния курортно-рекреационной отрясли Республики Крым - Друзин, Р.В.; Копачева, Е.И. (Культура народов Причерноморья, 2014)
В статье исследована динамика основных показателей курортно-рекреационного комплекса,
проведены сравнительный анализ показателей международного туризма и оценка современного состояния
курортно-рекреационного комплекса, выявлены основные проблемы развития. У статті досліджена динаміка основних показників курортно-рекреаційного комплексу, проведені
порівняльний аналіз показників міжнародного туризму і оцінка сучасного стану курортно-рекреаційного
комплексу, виявлено основні проблеми розвитку. The paper studies the dynamics of the main indicators of the resort and recreational complex, conducted a
comparative analysis of international tourism and assessment of the current state of the resort and recreational
complex, the basic problems of development.
Among the regions of Ukraine Republic of Crimea was in the top three (along with Kyiv and Ivano-Frankivsk region)
to 8 of 9 indicators ranking of regions on the main indicators of tourism development in 2011.
Considering the state of the tourism industry in the Republic of Crimea, in the first place, it should be noted favorable
conditions and rich recreational resources for treatment and recreation, tourism and sport.
Part of these problems can be solved in the near future, which is directly related to the reunification of the Crimea with
Russia and the planned establishment of the Republic of Crimea free economic zone.